(3MGTjI Ydi GdeOGQc hGdeSGddcs - (3GdHgHGfj, GdCUHgGfj, eMeO Ydj Hf eMeO HGbQ, J (B1216 (3g`s
(3ChdgG (B:s
(3CMeOg Ydi fhGdg (B... (3gPg MhGT JJVe ahGFO de CSHb EdjgG hYhGFO de CTQc GdJfHjg YdjgG ehSheI HGdaPGdc JLQj eLQi GdTQM Ydi cJGHj GdeOGQc hGdeSGdc aj TQM TQGFY GdESdGe GdeTJgQ Hjf GdNhGU hGdYhGe (B...s
(3BNQgG (B:s
... ... (3KdGKI CTjGA aEPG VQHfG fUa bWQg aj fUa GdMGUd aj VQHI aj KdGKI hSHY MUd SHYI hfUa SHY VQHfGg aj GdYeb MUd CMO hYTQhf (B... (3aj GdeOhOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\535s
(3GdPQjYI (B16 - 92(279)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis